2006
DOI: 10.1007/s00439-006-0304-0
|View full text |Cite
|
Sign up to set email alerts
|

A novel gene for Usher syndrome type 2: mutations in the long isoform of whirlin are associated with retinitis pigmentosa and sensorineural hearing loss

Abstract: Usher syndrome is an autosomal recessive condition characterized by sensorineural hearing loss, variable vestibular dysfunction, and visual impairment due to retinitis pigmentosa (RP). The seven proteins that have been identified for Usher syndrome type 1 (USH1) and type 2 (USH2) may interact in a large protein complex. In order to identify novel USH genes, we followed a candidate strategy, assuming that mutations in proteins interacting with this "USH network" may cause Usher syndrome as well. The DFNB31 gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
168
1
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(172 citation statements)
references
References 23 publications
2
168
1
1
Order By: Relevance
“…In addition, while many patients with Usher syndrome have significant vestibular dysfunction, 40 it is unclear whether patients with whirlin mutations (DFNB31 or Usher 2D) have vestibular deficits. 9,10,21,[41][42][43] None of the studies that reported on the phenotypes of these patients included detailed vestibular function tests. Therefore, additional studies are required to investigate the vestibular function in patients with whirlin mutations in order to gauge the potential therapeutic benefits of whirlin gene therapy on balance function in these patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, while many patients with Usher syndrome have significant vestibular dysfunction, 40 it is unclear whether patients with whirlin mutations (DFNB31 or Usher 2D) have vestibular deficits. 9,10,21,[41][42][43] None of the studies that reported on the phenotypes of these patients included detailed vestibular function tests. Therefore, additional studies are required to investigate the vestibular function in patients with whirlin mutations in order to gauge the potential therapeutic benefits of whirlin gene therapy on balance function in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…4,7 WHRN encodes a scaffolding protein called whirlin, which is required for normal hair cell stereocilia elongation. 8 Mutations in the WHRN gene can cause Usher syndrome type 2D (OMIM 611383), 9 as well as the non-syndromic autosomal recessive hearing loss DFNB31 (OMIM 607084). 10 The whirler mouse (Whrn wi/wi ) does not produce functional whirlin proteins in the inner ear, 11 resulting in abnormally short stereocilia in cochlear and vestibular hair cells.…”
Section: Introductionmentioning
confidence: 99%
“…Whirlin binds to the protein encoded by USH2A (18), a gene associated with both Usher syndrome type II (ARRP accompanied by hearing loss) and nonsyndromic ARRP (19). Whereas mutations in DFNB31 have been reported as rare causes of Usher syndrome type II (20,21), no DNA changes in its sequence have yet been associated with nonsyndromic ARRP. However, at the age of 66, the past medical history of this patient was significant for only hyperlipidemia and she did not report any hearing loss.…”
Section: Discussionmentioning
confidence: 99%
“…Whirlin contains three highly-conserved PDZ domains, mutations in which cause the 'whirler' phenotype in mice and prelingual-onset nonsyndromic deafness in humans, 36 including some types of Usher syndrome. 37 Like nucleoredoxin, the Usher protein complex is an effector of b-catenin, and also affects neuronal morphogenesis and structural plasticity. 38 Usher syndrome can cause central nervous system structural changes 39 and psychosis, 40 and there is one report of increased incidence of bipolar disorder among adults with prelingual-onset nonsyndromic deafness, 41 but it is not known if any of those patients carried the 'whirler' mutation.…”
Section: Ae Baum Et Almentioning
confidence: 99%